Biological Flora of the British Isles: Phragmites australis. (15th June 2017) - Packer, Jasmin G.; Meyerson, Laura A.; Skálová, Hana; Pyšek, Petr; Kueffer, Christoph
Summary: This account presents comprehensive information on the biology of Phragmites australis (Cav.) Trin. ex Steud. ( P. communis Trin.; common reed) that is relevant to understanding its ecological characteristics and behaviour. The main topics are presented within the standard framework of the Biological Flora of the British Isles : distribution, habitat, communities, responses to biotic factors and to the abiotic environment, plant structure and physiology, phenology, floral and seed characters, herbivores and diseases, as well as history including invasive spread in other regions, and conservation. Phragmites australis is a cosmopolitan species native to the British flora and widespread in lowland habitats throughout, from the Shetland archipelago to southern England. It is widespread throughout Ireland and is native in the Channel Islands. Native populations occur naturally in temperate zones and on every continent except Antarctica. Some populations in Australia and North America have been introduced from elsewhere and have become naturalized, and in North America, some of these are known to be invasive where they compete with native local populations of P. australis . Typical habitats in Britain range from shallow still water along waterbody edges to marshlands, saltmarshes and drier habitat on slopes up to 470 m above sea level. Additional habitats outside Britain are springs in arid areas, riverine lowlands (−5 m above sea level) and groundwater seepage points up to 3600 m above sea level. Although it occurs on a wide range of substrates and can tolerate pH from 2·5 to 9·8, in Britain it prefers pH >4·5 and elsewhere it thrives in mildly acidic to mildly basic conditions (pH 5·5–7·5). The species plays a pivotal role in the successional transition from open water to woodland. Phragmites australis is a tall, helophytic, wind‐pollinated grass with annual shoots up to 5 m above‐ground level from an extensive system of rhizomes and stolons. A single silky inflorescence develops at the end of each fertile stem and produces 500–2000 seeds. The plant is highly variable genetically and morphologically. Expansion of established populations is mainly through clonal growth of the horizontal rhizome system and ground‐surface stolons, while new populations can establish from rhizomes, stem fragments and seeds. Shoots generally emerge in spring, with timing determined primarily by physiology that is mediated by external conditions (e.g. local climate including frost). Many populations in the British Isles have experienced some decline over the past two decades and there is concern that there might be further losses along the east coast as sea level rises. There have recently also been localized expansions, especially in highly modified habitats, where P. australis reedbeds have been planted as wildlife habitat, rehabilitated mineral and gravel beds, and bioremediation filter beds for industrial and transport infrastructure. Native populations outside Britain also demonstrate both types of trend: they are declining in many parts of Western Europe and North America, yet also colonize many disturbed, ruderal habitats (e.g. the edges of agricultural fields and motorways) throughout its native and non‐native range and can form 'weedy' monodominant populations (e.g. in Australia and China). Abstract : Phragmites australis is a cosmopolitan species native to the British flora and widespread in lowland habitats. Native populations occur on every continent except Antarctica, from desert oases, river lowlands (−5 m a.s.l.) and up to groundwater seepage points at 3600 m above sea level, but are declining in Europe and North America. Infraspecific taxa within P. australis form a species complex with overlapping native and non‐native ranges.